MERAIH KEMAMPUAN DESAIN GRAFIS PROFESIONAL MELALUI PELATIHAN COREL DRAW UNTUK SMK - Ilham Albana; Ranggi Praharaningtyas Aji; Aulia Hamdi; Melia Dianingrum (Yayasan Nusantara Hasana Berdikari, 2023)
Graphic design is a rapidly growing field with plenty of career opportunities for those who have an interest and talent in this area. However, vocational high school students often face difficulties in developing graphic design skills and using graphic design software like Corel Draw. Therefore, this community engagement activity aims to provide solutions to the challenges faced by vocational high school students in learning graphic design. This community engagement activity consists of several stages, including observation, socialization with partners, creating a module for Corel Draw usage, content creation training, training evaluation, and overall engagement results evaluation. Through this initiative, it is hoped that vocational high school students will gain access and opportunities to attend graphic design training, receive clear guidance on applying graphic design software, stimulate their interest and enthusiasm for learning graphic design, and provide motivation and support for them to pursue a career as professional graphic designers. The results of this activity will enable participants to observe the improvement in graphic design skills among vocational high school students and help them prepare for entering the workforce or continuing their studies in graphic design. Therefore, this activity is expected to provide significant benefits for vocational high school students in developing graphic design skills and pursuing a career as skilled graphic designers.